1983
DOI: 10.1007/bf02125629
|View full text |Cite
|
Sign up to set email alerts
|

Amyotrophic lateral sclerosis in the province of Parma, Italy: a clinical and epidemiological study in the period 1960–1980

Abstract: A clinical and epidemiological study on ALS was conducted in the province of Parma, Italy, in the period 1960-1980. A total of 78 cases was collected from hospital records. The average annual incidence was 0.93 per 100,000 with no difference between rural and urban areas. On prevalence day (October 24, 1971) a prevalence rate of 2.27 was found. Mean age at onset was 59 years, with no sex difference. In 70% of cases the onset was between 50 and 70 years, this datum being statistically significant (p less than 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
1

Year Published

1990
1990
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 11 publications
2
3
1
Order By: Relevance
“…The age−incidence curve was similar for both sexes, although in our study women reached the peak of incidence slightly later than men. A slight and not significant higher incidence has been recorded amongst women in agreement with some other reports . All other clinical and demographic characteristics agreed with those reported in the literature .…”
Section: Discussionsupporting
confidence: 92%
“…The age−incidence curve was similar for both sexes, although in our study women reached the peak of incidence slightly later than men. A slight and not significant higher incidence has been recorded amongst women in agreement with some other reports . All other clinical and demographic characteristics agreed with those reported in the literature .…”
Section: Discussionsupporting
confidence: 92%
“…The mean annual ALS incidence rates observed by us for the last decade, are quite similar to those obtained in other Italian regions (21,(23)(24)(25)(26)(33)(34)(35)(36). The only exception is the province of Parma where values of 0.93/100,000 inhabitants were obtained (27) which are slightly higher than those observed elsewhere. With regard to other foreign countries, data obtained tend to agree with our results.…”
Section: Discussionsupporting
confidence: 87%
“…On the contrary, the increase of bulbar forms we observed in the last decade is a peculiar finding which has been reported in literature, so far as we know, only by Juvarra et al (27). To date it has not been possible to interpret the significance of this finding.…”
Section: Discussioncontrasting
confidence: 59%
“…While the above studies provide some evidence to suggest rural area involvement in ALS, whether directly or indirectly as a factor, there is also evidence to suggest the contrary. Although living in suburban ( 34 ) or urban areas ( 34 , 35 , 43 45 , 47 , 48 ) were not associated with the risk of ALS in any of the included studies, three out of the seven studies categorizing place of residence into various levels of urbanization found a significant positive association between those living in more highly urbanized/dense areas and the risk of ALS ( 36 , 50 , 53 ). As opposed to the often poorly defined or absent definitions of rural vs. urban areas in the other studies, level of urbanization in these studies were determined by set cut-offs using number of inhabitants, population density or addresses/km 2 .…”
Section: Resultsmentioning
confidence: 89%
“…Of those, two found a significant positive association or correlation between ALS and rural areas ( 35 , 46 ) and two noted a higher percentage of patients from rural areas than the estimated number of the rural population ( 43 , 44 ). The other five studies found no association ( 32 34 , 45 , 47 ), including one case-control study that considered previous history of rural residence for various durations via structured interviews ( 33 ). Among the four studies noting a positive relation to ALS, over-representation of elementary occupations, such as laborers in agriculture, mining, manufacturing and transport ( 43 ), or farmers ( 46 ) were noted.…”
Section: Resultsmentioning
confidence: 99%